Influence of tropical cyclone moving speeds on the attenuation effect of Holland surface wind and storm surge simulation in Guangdong Province, China - Yazhou Ning; Xianwei Wang; Yongjun Fang; Peiqing Yuan (Geomatics, Natural Hazards & Risk)
The Holland wind model remains limitations on the accurate surface wind estimation of tropical cyclone (TC) and the storm surge modelling. This study investigates the influence of TC moving speeds on the attenuation effect of Holland surface wind and proposes a weakening factor to correct Holland surface wind. Then the corrected surface wind fields are combined with ERA5 to produce the improved hybrid surface wind fields to simulate total water levels. The significant linear correlation (R2 = 0.54) between TC moving speeds and the weakening factor shows that the slower the TC moves, the greater attenuation rate the surface wind speeds need. The improved Hybrid wind fields (Hybrid_f) have the best agreement with ground observations, with the Skills and RMSEs in the range of 0.65-0.93 and 2.3-6.9 m/s. The total water levels of storm surge simulated by the Hybrid_f have the best agreement with gauge measurements, with the Skills and RMSEs in the range of 0.72-0.99 and 0.16-0.51 m. In particular, the improved surface wind fields for TCs with slower movement substantially mitigate the severe reduction of water levels. These findings offer valuable insights for optimizing the surface wind fields to improve storm surge modeling and other applications.